Predictability of the realised volatility of international stock markets amid uncertainty related to infectious diseases - Sisa Shiba; Juncal Cu\~nado Eizaguirre; Rangan Gupta (Journal of Risk and Financial Management, 2022)
In the context of the great turmoil in the financial markets caused by the COVID-19 pandemic, the predictability of daily infectious diseases-related uncertainty (EMVID) for international stock markets volatilities is examined using heterogeneous autoregressive realised variance (HAR-RV) models. A recursive estimation approach in the short-, medium- and long-run out-of-sample predictability is considered and the main findings show that the EMVID index plays a significant role in forecasting the volatility of international stock markets. Furthermore, the results suggest that the most vulnerable stock markets to EMVID are those in Singapore, Portugal and The Netherlands. The implications of these results for investors and portfolio managers amid high levels of uncertainty resulting from infectious diseases are discussed.
Keywords: 330; uncertainty; infectious diseases; COVID-19; international stock markets; realised volatility; forecasting